KARAKTERISTIK FISIKOKIMIA DAN SENSORI VLA LABU PARANG (CUCURBITA MOSCHATA DURCH) - Mardiah Mardiah (Jurnal Pertanian, 2021)
This study aims to utilize Cucurbita Moschata D in processed products in the form of custard. There are three research stages; the first stage is making pumpkin puree, the second stage is determining the concentration of pumpkin puree and cornstarch to get the best custard texture. Then, Compare the concentration of granulated sugar (25%, 27.5%, 30%, 32.5%, 35%) with two replications on the shelf life of custard, the third stage. The research used a completely randomized design with one treatment factor comparing pumpkin puree with cornstarch with two repetitions. Product analysis includes organoleptic tests (sensory and hedonic tests), physical and chemical, and proximate tests. The first stage results showed that the ratio of pumpkin and cornstarch (16.6%: 5%) produced the best texture. This formula's chemical and physical tests were water content 7.81%, ash 0.084%, fat 7.53%, protein 9.02%, antioxidant activity 649,594 ppm, and beta carotene 175.53 g/g. The results of the test of water content, pH, and TPC showed the best treatment at the concentration of granulated sugar (32.5%) with storage time on the 1st, 3rd, 6th, and 9th days.